The Influence Of Differentiated Learning On Phase C Science Learning Outcomes In Primary Schools - Alwi Muslimin, Nur Wahyuni Ainul; Achmad, Widya Karmila Sari; Usman, Hikmawati (Program Studi PGSD FIP UNM, 2024)
The purpose of this experimental study is to: 1. Ascertain how varied instruction affects students' learning results at the IPAS in primary schools. 2. To find out an overview of the results of stage C IPAS in elementary schools. 3. To determine whether or not there is an influence of differentiated learning on IPAS outcomes at stage C in elementary schools. The independent variable in this research is learning differentiation, while the dependent variable is students' IPAS outcomes. The population in this study was class V UPT SD Negeri 12 Bontoramba students, Bontoramba District, Jeneponto Regency, consisting of 45 students, class V A as the experimental class and class VA B as the control class. Sample determination was carried out using a saturated sampling technique. Based on the results of descriptive statistical analysis, it is known that the science learning outcomes of experimental and control class students have increased, but the experimental class shows a more significant increase. This is based on the average of the experimental class in the pretest being in the low category and then in the posttest being in the high category. The results of inferential statistical analysis show that Equal variance is not assumed, the Sig (2-tailed) value is smaller than the α value, meaning that H0 is rejected and Ha is accepted. This shows that there is a significant influence between the application of the differentiation learning model IPAS outcomes at the initial stage C in elementary schools.